THE RELATIONSHIP OF D-DIMER LEVELS WITH RISK FOR DEVELOPING DEEP-VEIN THROMBOSIS AND/OR PULMONARY THROMBOEMBOLISM AFTER ORTHOPAEDIC TRAUMA SURGERY - Naeem, MA; Usman, M; Latif, MK; Aamir, M (Journal of Ayub Medical College Abbottabad, 2009)
Background: Deep venous thrombosis (DVT) and pulmonary embolism (PE) are common complications in trauma patients. Fibrin-related markers (FRMs), such as fibrin and fibrinogen degradation products (FDPs), D-dimer, and soluble fibrin (SF), are considered to be useful for the diagnosis of thrombosis (DVT). Objective: We report on 3-month follow-up of fibrinolytic activity after Orthopaedic Trauma Surgery (OTS). Methods: Patients who entered the study were divided into (group 1) patients who did not develop DVT/PE after OTS while patients who developed DVT/PE were included in (group 2). Blood samples were obtained on day of surgery and postoperative days 1, 7 and 30, and assayed for blood counts, C-reactive protein (CRP), and Ddimers. Demographic and clinical data were also collected. Results: Postoperative levels of Ddimers of both groups increased on day 1, and remained elevated on day 30. Postoperative levels of D-dimers on day 1, 7 and 30 were higher in group 2 (p<0.05). There were no differences in perioperative levels of CRP between groups, and they correlated with D-dimers both preoperatively and on day 30. Taken together, these data suggest that orthopaedic trauma surgery induced an activation of coagulation and fibrinolysis. This situation lasts at least as late as 30 days after surgery. Conclusion: The D-dimer levels were significantly higher in patients developing DVT/PE post OTS. Keywords: D-dimer, DVT, Deep Vein Thrombosis, Pulmonary Embolism